Subjunctive mood in Croatian: non-temporal use of tense - Geld, Renata (2004)
The subjunctive mood is nowhere explicitly mentioned in grammars of Croatian and there are no separate verb paradigms for the subjunctive as we find them in languages such as French. However, aside from the indicative and imperative, the conditional is cited as a third mood in Croatian. The conditional mood has a separate paradigm of verb forms (the present and past conditional) used not only in conditional clauses (the so-called if-clauses), but also to express a whole range of subjunctive meanings: wishes, demands, proposals, concession, etc. Moreover, the Croatian language employs several other forms to signal irrealis: the present tense (both perfective and imperfective), the perfective future forms and the past perfect tense. This paper focuses on the ways in which Croatian tenses are used to indicate irreality, as described in Langacker's basic epistemic model (Langacker, 1991). We would like to argue that the Croatian grammar lacks an appropriate description of irrealis meaning signalled by tense morphology that marks the degrees of actuality. More specifically, we propose that in the modern Croatian language there are two perfective tenses, the perfective present and the perfective future, that consistently appear in clauses that establish mental spaces with non-canonical viewing arrangement (Fauconnier, 1997 ; Langacker, 2001). We start by re-analysing Croatian if-clauses. In the Croatian language there are three subordinators, ako ('if'), kad ('if', 'when') and da ('if'), whose semantic value lies in introducing either anticipated or virtual reality (Langacker, 2001). We concentrate on the present tense (both imperfective and perfective) used in subordinate clauses and provide evidence of the importance of non-canonical viewing arrangement in understanding the Croatian verb system. We analyse what kind of mental spaces the mentioned subordinators open. We describe and compare the degrees of hypothesis they contain. We suggest that Croatian subordinators ako ('if'), kad ('if'', 'when') and da ('if') when followed by either the imperfective or perfective present create mental time frames where the usage of present is motivated by its inherent value of describing an event coinciding with the time of speaking. In his description of the English present tense and its non-temporal usage, Langacker points out that „ the scheduled future strongly favours a time expression“ (Langacker, 2001:267). It is our intention to demonstrate that a role analogous to the one of time expression can be assigned to the three subordinators when describing their relation to the mental time frames. Their role is evident in cases where they are used to signal epistemic distance, for example: Da učim, prošao bih na ispitu ('If I studied, I would pass the exam'), Ako učim, prođem na ispitu ('If I study, I pass the exam'), Kad učim, prođem na ispitu ('When I study, I pass the exam'). Following Fauconnier's (1997) work on mental spaces, we are looking at the nature of conditional spaces established by the three subordinators and the change of their configuration due to the hypothetical premise they propose. At this point we introduce examples which support our claim that the usage of the perfective present and perfective future is exclusively non-temporal. Furthermore, we provide evidence that in a great number of cases they signal irrealis meaning. Let us consider the following examples: 1) Sutra ide-m u kin-o. tomorrow go.IMPF-1sg.PRES to cinema-ACC.sg.NEUT 'Tomorrow I am going to the cinema.' 2) **Sutra ode-m u kino. go.PERF-1sg.PRES 3) Sutra ć-u i-ći u kino. want.IMPF.AUX-1sg go-INF.IMPF 'Tomorrow I will go to the cinema.' 4) ?Sutra bude-m iša-o-&Oslash ; u kino. be.PERF.AUX-1sg go.IMPF-PAST-3sg.M In the example (1) the imperfective present is used to express a fixed plan in future. It is a typical and very common non-present usage of the Croatian present. The example (2) is not acceptable since the perfective present cannot be used in independent clauses. In the example (3) the future tense (the so-called future I) is used to express future and in the example (4) the perfective future (the so-called future II) is used to express future. The sentence (4) is marked with a question mark since some non-standard varieties of Croatian would allow for this of usage. However, both the perfective present and perfective future are perfectly acceptable in the following examples: 5) Ako ode-m u kino, nema šanse da završim posao. if go.PERF-1sg.PRES 'If I went to the cinema, there is no way I could finish the work.' 6) Ako bude-m iša-o-&Oslash ; u kino, nema šanse da završim if be.PERF.AUX-1sg go.IMPF-PAST-3sg.M posao. 'If I went to the cinema, there is no way I could finish the work.' In both (5) and (6) ako ('if') + the perfective present / future establish a mental space that corresponds to what Langacker (2001) has named a virtual document. The construction described introduces virtual reality where the action of 'going to the cinema' happens only in the sense of being an item in the virtual document. Furthermore, the perfective present is acceptable in all of the following examples: 7) Kad(god) pomisli-m na njega, osjećam se bolje. when(ever) think.PERF-1sg.PRES feel-1sg.PRES 'Whenever I think of him, I feel better.' 8) Ako pomislim na njega, osjećam se bolje. if 'If I think of him, I feel better.' 9) Da pomisli-m na njega, osjećala bih se bolje. if think.PERF-1sg.PRES feel.COND.PRES 'If I thought of him, I would feel better.' In (7) and (8) kadgod ('whenever') / kad ('when') / ako ('if') + perfective present is followed by the present while in (9) da ('if') + perfective present is followed by the Croatian present conditional. All four subordinators signal virtual reality. The example with da opens a mental space with greater epistemic distance. The perfective future is used as follows: 10) Kad(god) bude-m ima-l-a novaca, kupit ću knjigu. when(ever) be.PERF.AUX-1sg have-PAST-3sg.F buy.1sg.FUT 'When(ever) I will have the money, I will buy a book.' 11) Ako budem imala novaca, kupit ću knjigu. if 'If I will have the money, I will buy a book.' 12) Nikada neću baciti knjigu koju bude-m kupi-l-a. never not.throw.FUT.1sg be.PERF.AUX-1sg buy.PERF-PAST-3sg.F 'I will never throw away the book which I will have bought.' 13) Dobit će olakšice kakve budu tražili. get.FUT.3pl be.PERF.AUX-3pl demand.IMPF-PAST-3pl.M 'They will get all the privileges they will have asked for.' So, finally, we have looked at what kind of virtual reality is established by the perfective future. The role of the perfective future used in subordinate clauses is to express an imaginary event prior to the event described in the main clause. Due to different subordinators, the examples (10) and (11) differ in epistemic distance. In the example (12) and (13) it is used in relative clauses. It again refers to imaginary events preceding those in the main clauses. Before we conclude, it is important to mention that the translations into English do not clearly reflect the meanings signalled by the forms we are trying to label as Croatian subjunctive. Dimensions of irrealis are numerous. Traditional grammars have certainly lacked the tools to tackle these dimensions and underlying cognitive constructs created by round-the-clock communication between language and mind. We would like to finish by concluding that both the perfective present and perfective future do deserve to be cited as the Croatian subjunctive that is consistently used to signal irrealis. Both tenses regularly open and construct mental spaces that depart from the canonical viewing arrangement. The speaker does not describe what is observed but what is imagined, predicted or desired, so a fictive vantage point becomes crucial for construing the given situation from the point other than the time of speaking.